Luxembourg : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper studies the fiscal and macroeconomic impact of different reform options. It analyzes the impact of an increase in the contribution rate, a reduction of benefits, and an increase in the retirement age. Although all reform options can lead to the fiscal sustainability of the system, there are important macroeconomic trade-offs among them. Although the Luxembourg's pension system is sound over the near term, further reforms are needed to ensure its long-term sustainability. This paper explored the fiscal and macroeconomic impact of several reform options: an increase in the contribution rate, a reduction of benefits, and an increase in the retirement age. Although all these reforms would help ensuring fiscal long-term sustainability, there are important macroeconomic trade-offs. Even though an increase in contribution rates can be implemented immediately, it introduces distortions in the labor market which lead to a decline in GDP in addition to a decline in consumption.